Osteonecrosis of the jaw risk factors in bisphosphonate‐treated patients with metastatic cancer. (14th December 2020) - Van Poznak, Catherine; Reynolds, Evan L.; Estilo, Cherry L.; Hu, Mimi; Schneider, Bryan Paul; Hertz, Daniel L.; Gersch, Christina; Thibert, Jacklyn; Thomas, Dafydd; Banerjee, Mousumi; Rae, James M.; Hayes, Daniel F.
Abstract: Background: A case–control study was performed to define clinical and genetic risk factors associated with osteonecrosis of the jaw in patients with metastatic cancer treated with bisphosphonates. Methods: Clinical data and tissues were collected from patients treated with bisphosphonates for metastatic bone disease who were diagnosed with osteonecrosis of the jaw (cases) and matched controls. Clinical data included patient, behavioral, disease, and treatment information. Genetic polymorphisms in CYP2C8 (rs1934951) and other candidate genes were genotyped. Odds ratios from conditional logistic regression models were examined to identify clinical and genetic characteristics associated with case or control status. Results: The study population consisted of 76 cases and 126 controls. In the final multivariable clinical model, patients with osteonecrosis of the jaw were less likely to have received pamidronate than zoledronic acid (odds ratio = 0.18, 95% Confidence interval: 0.03–0.97, p = .047) and more likely to have been exposed to bevacizumab (OR = 5.15, 95% CI: 1.67–15.95, p = .005). The exploratory genetic analyses suggested a protective effect for VEGFC rs2333496 and risk effects for VEGFC rs7664413 and PPARG rs1152003. Conclusions: We observed patients with ONJ were more likely to have been exposed to bevacizumab and zoledronic and identified potential genetic predictors that require validation prior to clinical translation.